Transfusão feto-fetal – sobrevivente policitémico - Dias, Joana (2014)
Introduction: Twin-twin transfusion syndrome (TTTS) is associated with the death of one or both foetuses, particularly if diagnosed before 28 weeks’ gestation. Sudden deteriorations can occur, leading to death of the cotwin and neurological handicap in the survivor. Case Report: We report a case of polycythemia in the recipient twin of a pregnancy with TTTS. Laser photocoagulation of placental anastomoses was performed successfully at 18 weeks. Follow-up showed resolution of signs of TTTS on ultrasound examination. Caesarean section at 33 weeks due to foetal death of donor twin, the recipient twin demonstrated symptomatic polycythemia (hematocrit 70%). Partial exchange transfusion (PET) was performed twice in the first 12 hours. Normal hematocrit levels were achieved without complication. Perinatal outcome was good. Conclusion: Despite the prognosis improvement after laser photocoagulation of placental anastomoses, perinatal mortality and morbidity remains height.